Pengaruh Penempatan Kerja dan Lingkungan Kerja pada PT. Haleyora Power Region 4 Sumatera Barat - Jesika Kiranda; Vicky Brama Kumbara; Chintya Ones Charly (JURNAL RISET MANAJEMEN (JURMA), 2025)
This research aims to examine the influence of work placement and work environment on employee performance with job satisfaction as an intervening variable using primary data obtained by distributing questionnaires to 100 employees as respondents, namely at PT. Haleyora Power Region 4 West Sumatra. In this research, Structural Equation Modeling (SEM) analysis tools were used using Partial Least Square (PLS). The results show that Job Placement has a positive and significant effect on Job Satisfaction at PT. Haleyora Power Region 4 West Sumatra, There is a Work Environment that has a positive and insignificant effect on Job Satisfaction at PT. Haleyora Power Region 4 West Sumatra, Work Placement has a positive and insignificant effect on Employee Performance at PT. Haleyora Power Region 4 West Sumatra, There is a Work Environment that has a positive and significant impact on Employee Performance at PT. Haleyora Power Region 4 West Sumatra, Job Satisfaction has a positive and significant effect on Employee Performance at PT. Haleyora Power Region 4 West Sumatra, Job Placement through Job Satisfaction has a positive and insignificant effect on Employee Performance at PT. Haleyora Power Region 4 West Sumatra, There is a Work Environment through which Job Satisfaction has a positive and significant effect on Employee Performance (Y) at PT. Haleyora Power Region 4 West Sumatra.